The role of management accounting techniques in determining the relationship between purchasing and supplier management: A case study of retail firms in Kazakhstan - Miyazhdenovna, N.A.; Zhaslanovna, S.E.; Anuarbekkyzy, G.N.; Nurlanovna, L.A.; Tulegenovna, Kh.Zh. (Uncertain Supply Chain Management, 2020)
The main concern of the current empirical research is to examine the role of management accounting techniques in determining the relationship between purchasing and supplier management in the retail sector of Kazakhstan, which during the last four years, has grown significantly. This study is based on the premise that managerial accounting is aligned with many factors such as quality, reliability, and price along with make-or-buy analysis, supplier certifications, value analysis, and certification as well. Besides, planning and sharing of information and holding ethical standards can also be aligned with managerial accounting. Employing a survey-based methodology, the SEM-PLS technique is used as a statistical tool to test the hypothesized relationships and answer the research questions of this study. The findings of the study provide support to the theoretical framework and a ground to examine the hypotheses of the current study. The results reveal that the cost of purchased goods did not represent only the purchasing element but also such factors like quantity and quality of goods and delivery time that can significantly influence any organizational operations. The study reiterates that the basic purpose of managerial accounting with reference to purchasing is the formulation and execution of a purchasing plan for goods with the supporting operation strategies. These findings will be helpful for policymakers and practitioners to understand the issues related to management accounting techniques and determine the relationship between purchasing and supplier management in the retail sector.
Keywords: management accounting; purchasing; supplier management; Kazakhstan